2001
DOI: 10.3133/ofr01338
|View full text |Cite
|
Sign up to set email alerts
|

Results of a monitoring program of continuous water levels, specific conductance, and water temperature at the OK Tool Facility of the Savage Municipal Well Superfund Site, Milford, New Hampshire

Abstract: Vertical Datum: In this report "NGVD-29" refers to the National Geodetic Vertical Datum of 1929 (NGVD of 1929) a geodetic datum derived from a general adjustment of the first-order level nets of both the United States and Canada, formerly called Sea Level Datum of 1929. Contents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Other studies by the USGS include construction and calibration of two groundwater-flow models (Harte and others, 1999;Harte and Mack, 1992), evaluation of the effects of groundwater withdrawals on advective transport of contaminated groundwater (Harte and Willey, 1997), analysis of PCE trends for pre-and post-barrier conditions (Harte and others, 2001), and description of a monitoring program of continuous water levels from water years 1997-2003 (Brayton and Harte, 2001;and Harte, 2005). Simulation of solute transport of PCE for the OU1 and OU2 areas is described in Harte (2004), and testing of remedial hydraulic operational schemes is described in Harte (2006).…”
Section: Previous Investigations Of Operable Unit 1 (Ou1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies by the USGS include construction and calibration of two groundwater-flow models (Harte and others, 1999;Harte and Mack, 1992), evaluation of the effects of groundwater withdrawals on advective transport of contaminated groundwater (Harte and Willey, 1997), analysis of PCE trends for pre-and post-barrier conditions (Harte and others, 2001), and description of a monitoring program of continuous water levels from water years 1997-2003 (Brayton and Harte, 2001;and Harte, 2005). Simulation of solute transport of PCE for the OU1 and OU2 areas is described in Harte (2004), and testing of remedial hydraulic operational schemes is described in Harte (2006).…”
Section: Previous Investigations Of Operable Unit 1 (Ou1)mentioning
confidence: 99%
“…Harte (2006) reported that the capture areas for the interior barrier extraction wells are smaller than anticipated because of groundwater upflow from the underlying bedrock, based on numerical groundwater-flow simulations of remedial operations. The hydraulic connection between the overburden and underlying bedrock was identified from water-level responses during remedial operations (Brayton and Harte, 2001;and Harte, 2005).…”
Section: Previous Investigations Of Operable Unit 1 (Ou1)mentioning
confidence: 99%
“…Brayton and Harte (2001) showed that recharge rates inside the barrier area decreased by as much a half from pre-construction periods because of the addition of a semiconical, land-surface cap during barrier-wall construction.…”
Section: Simulation Of Solute Transport Of Tetrachloroethylene 35mentioning
confidence: 99%